Time evolution of methotrexate-induced kidney injury: A comparative study between different biomarkers of renal damage in rats - Severin, María Julia (2019)
Methotrexate (MTX) is commonly used in the treatment of malignant diseases and autoimmune and chronic inflammatory disorders. Along with its effective therapeutic power, MTX has adverse effects on the kidneys. Discovery of new biomarkers is required to improve the early detection of renal damage and optimize the effectiveness of treatments. The aim of this study was to evaluate the time course of MTX-induced nephrotoxicity and to compare the urinary excretion of the organic anion transporter 5 (uOat5) with alterations in other markers of renal function, and to elucidate the possible molecular mechanisms involved in uOat5. Animals were exposed to a unique dose of MTX (80 mg/kg body weight, intraperitoneal). Experiments were carried out at days 2, 4, 8 or 14 after MTX administration. Markers of renal damage, such as creatinine and urea plasma levels, urinary activity of alkaline phosphatase, microalbuminuria, urinary excretion of neutrophil gelatinase-associated lipocalin (uNGAL) and histopathology, were evaluated. Renal organic anion transporter 5 (Oat5) expression and its presence in different urine fraction were assessed by western blotting. uOat5 was significantly increased 2 days after MTX treatment, before than any alteration in other parameters of kidney injury or renal morphology occurred. uNGAL showed an inverted pattern of urinary excretion compared to uOat5. Exosomal pathway is involved in the urinary excretion of Oat5 and depends on the degree of damage induced by MTX. These experimental data allow proposing uOat5 as a potential non-invasive biomarker for early detection of MTX-induced nephrotoxicity.